Ukraine - Country Economic Memorandum : Strategic Choices to Accelerate and Sustain Growth - World Bank (World Bank, 2012)
This report undertakes a comprehensive assessment of Ukraine's growth experience over the past decade. It shows how vulnerabilities were allowed to accumulate during the economic boom. And how growth, averaging seven percent annually between 2000 and 2008, was achieved without tackling Ukraine's well known weaknesses in the investment climate and public sector governance. The report also traces the emergence of large structural fiscal deficits and fiscal pressures since 2004, as buoyant revenues and terms of trade gains masked an increasingly unsustainable fiscal position. It shows how international excess liquidity allowed Ukraine to attract vast capital flows, intermediated through the banking system, while financial sector regulation remained inadequate. And it analyzes how a poor investment climate, low competitive pressures, limited innovation and slow structural transformation of the economy are all interlinked and perpetuate Ukraine's dependence on a few commodity based exports. Consequently, the report argues, the route to sustained recovery in Ukraine lies in deepening key reforms. The report carries out an in-depth diagnostic of Ukraine's growth drivers at the macro, sector and firm-level and derives key constraints to sustained growth from this analysis. The recommendations point to three main challenges that deserve priority attention if Ukraine is to re-launch its economy on a sustained growth path. First, Ukraine has to tackle its fiscal crisis to restore macroeconomic credibility and create fiscal space for investments needed to support private sector growth. Second, Ukraine needs to improve its investment climate and fix the financial system to attract private sector investment. Third, Ukraine needs to tackle the problems with public sector governance through deep public sector, judicial and administrative reforms. Since this is a large agenda, the analysis identifies short and medium term priorities. The report also argues that the key reforms highlighted above are closely interlinked and that cosmetic and halfway measures will not do.